Negative regulation of the interferon response by an interferon-induced long non-coding RNA. Issue 16 (13th August 2014) - Kambara, Hiroto; Niazi, Farshad; Kostadinova, Lenche; Moonka, Dilip K.; Siegel, Christopher T.; Post, Anthony B.; Carnero, Elena; Barriocanal, Marina; Fortes, Puri; Anthony, Donald D.; Valadkhan, Saba
Abstract: Long non-coding RNAs (lncRNAs) play critical roles in diverse cellular processes; however, their involvement in many critical aspects of the immune response including the interferon (IFN) response remains poorly understood. To address this gap, we compared the global gene expression pattern of primary human hepatocytes before and at three time points after treatment with IFN-α. Among ∼200 IFN-induced lncRNAs, one transcript showed ∼100-fold induction. This RNA, which we named lncRNA-CMPK2, was a spliced, polyadenylated nuclear transcript that was induced by IFN in diverse cell types from human and mouse. Similar to protein-coding IFN-stimulated genes (ISGs), its induction was dependent on JAK-STAT signaling. Intriguingly, knockdown of lncRNA-CMPK2 resulted in a marked reduction in HCV replication in IFN-stimulated hepatocytes, suggesting that it could affect the antiviral role of IFN. We could show that lncRNA-CMPK2 knockdown resulted in upregulation of several protein-coding antiviral ISGs. The observed upregulation was caused by an increase in both basal and IFN-stimulated transcription, consistent with loss of transcriptional inhibition in knockdown cells. These results indicate that the IFN response involves a lncRNA-mediated negative regulatory mechanism. lncRNA-CMPK2 was strongly upregulated in a subset of HCV-infected human livers, suggesting a role in modulation of the IFN response in vivo .